The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11096-017-0513-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist intervention acceptance for the reduction of potentially inappropriate drug prescribing in acute psychiatry

Abstract: Background Prescribing for the elderly is challenging. A previous observational study conducted in our geriatric psychiatry admission unit (GPAU) using STOPP/START criteria showed a high number of potentially inappropriate drug prescriptions (PIDPs). A clinical pharmacist was added to our GPAU as a strategy to reduce PIDPs. Objective The objective of the present study was to assess the impact of a clinical pharmacist on PIDPs by measuring acceptance rates of pharmacist interventions (PhIs). Setting This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…This result indicated that the medical team rejection to the clinical pharmacist interventions has to be taken as a tool to improve educational and communication skills of clinical pharmacist and their interns. However, these results go well with the results from Hannou et al when they used two different techniques (STOP/START) where the total acceptance rate for clinical pharmacist ' s interventions was Implementation of clinical pharmacy service in a tertiary psychiatric hospital in Aseer region, Saudi Arabia: 15month experience 44% and 58% for STOP and START techniques respectively [12]. In the other hand, our improvement in response results will be comparable with the expectations of psychiatrists in Saudi Arabia toward clinical pharmacists when it has shown that 70% of psychiatrists see the clinical pharmacist as a reliable source of drug in neuropsychiatric field [26].…”
Section: Alshahrani/abosamra/khobranisupporting
confidence: 86%
See 1 more Smart Citation
“…This result indicated that the medical team rejection to the clinical pharmacist interventions has to be taken as a tool to improve educational and communication skills of clinical pharmacist and their interns. However, these results go well with the results from Hannou et al when they used two different techniques (STOP/START) where the total acceptance rate for clinical pharmacist ' s interventions was Implementation of clinical pharmacy service in a tertiary psychiatric hospital in Aseer region, Saudi Arabia: 15month experience 44% and 58% for STOP and START techniques respectively [12]. In the other hand, our improvement in response results will be comparable with the expectations of psychiatrists in Saudi Arabia toward clinical pharmacists when it has shown that 70% of psychiatrists see the clinical pharmacist as a reliable source of drug in neuropsychiatric field [26].…”
Section: Alshahrani/abosamra/khobranisupporting
confidence: 86%
“…From the literatures, the acceptance rate of clinical pharmacist ' s interventions within psychiatric team showed optimism among clinicians where it was equal or more than 70% from either clinical pharmacists or clinical pharmacy residents [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Hannou et al 31 introduced a part-time ward-based clinical pharmacist to a psychiatric unit’s multidisciplinary team and screened prescriptions for potentially inappropriate drug prescribing using the STOPP/START criteria. The intervention was measured by the acceptance rate of pharmacist interventions.…”
Section: Resultsmentioning
confidence: 99%
“…It extends the findings of Goldstone et al 21 and others [87][88][89] by highlighting recent work done by psychiatric pharmacists on patient-level outcomes. Many previous studies [90][91][92] describe the impact of pharmacist-performed comprehensive medication reviews and medication management services by highlighting only the number of drug-related problems identified or the number of pharmacist-suggested interventions accepted by the treatment team. Although useful, these findings do not measure the impact of the psychiatric pharmacist directly on patient outcomes, such as symptom control, quality of life, or need for hospitalization.…”
Section: Discussionmentioning
confidence: 99%